2014
DOI: 10.1371/journal.pone.0106589
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Profiling of the Polyamine Content in Enteroinvasive E. coli : Looking into the Gap between Commensal E. coli and Harmful Shigella

Abstract: Polyamines are small molecules associated with a wide variety of physiological functions. Bacterial pathogens have developed subtle strategies to exploit polyamines or manipulate polyamine-related processes to optimize fitness within the host. During the transition from its innocuous E. coli ancestor, Shigella, the aetiological agent of bacillary dysentery, has undergone drastic genomic rearrangements affecting the polyamine profile. A pathoadaptation process involving the speG gene and the cad operon has led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…It has been demonstrated that a higher level of spermidine increases Shigella survival within macrophages and confers higher resistance to oxidative stress (Barbagallo et al., ), indicating that the loss of speG function is an emerging trait. As predicted, EIEC have an intermediate position as active N‐acetylspermidine is still present in most EIEC strains (68.7% in our dataset), yet intracellular spermidine tends to be higher as compared to commensal E. coli (Campilongo et al., ). Interestingly, among all non‐ Shigella strains that were sent to the NRCS by peripheral Belgian laboratories, not a single strain with defective speG was detected (Appendix 2), strongly suggesting that the large majority are non‐EIEC strains.…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that a higher level of spermidine increases Shigella survival within macrophages and confers higher resistance to oxidative stress (Barbagallo et al., ), indicating that the loss of speG function is an emerging trait. As predicted, EIEC have an intermediate position as active N‐acetylspermidine is still present in most EIEC strains (68.7% in our dataset), yet intracellular spermidine tends to be higher as compared to commensal E. coli (Campilongo et al., ). Interestingly, among all non‐ Shigella strains that were sent to the NRCS by peripheral Belgian laboratories, not a single strain with defective speG was detected (Appendix 2), strongly suggesting that the large majority are non‐EIEC strains.…”
Section: Discussionsupporting
confidence: 82%
“…Enteroinvasive E. coli are evolutionary intermediates between E. coli and Shigella . 78 Some of the enteroinvasive E. coli (EIEC) may cross-react with Shigella anti-sera. It should be noted that serological testing of the serum of an infected individual is generally not useful for diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…(E) Identification of the VirF 21 binding site on the virF promoter based on DNase I footprinting results. Plasmid pMYSH6504 DNA (41) was incubated with 0, 10 or 20 µl of in vitro -translated VirF 21 . The samples were DNase I treated and subsequently analyzed as described in Materials and Methods, using ML-U30 and ML-U29 as primers.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA from exponentially growing plasmid-carrying E. coli strains was extracted (41). Total RNA (10 to 20 µg) was hybridized with 5′- 32 P-labeled ML-512 and ML-1314 primers.…”
Section: Methodsmentioning
confidence: 99%